2017
DOI: 10.3389/fncir.2017.00014
|View full text |Cite|
|
Sign up to set email alerts
|

Reconsidering Tonotopic Maps in the Auditory Cortex and Lemniscal Auditory Thalamus in Mice

Abstract: The auditory thalamus and auditory cortex (AC) are pivotal structures in the central auditory system. However, the thalamocortical mechanisms of processing sounds are largely unknown. Investigation of this process benefits greatly from the use of mice because the mouse is a powerful animal model in which various experimental techniques, especially genetic tools, can be applied. However, the use of mice has been limited in auditory research, and thus even basic anatomical knowledge of the mouse central auditory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 76 publications
3
41
1
Order By: Relevance
“…This could be addressed via systematic projection mapping between the auditory cortex and the amygdala. In the current study, we visualized comprehensive connectivity between the auditory cortex and the amygdala by injecting cholera toxin subunit b (CTB), a bidirectional tracer, into four tonotopic regions of the auditory cortex, according to a map that was functionally determined using flavoprotein fluorescence imaging (Tsukano et al, 2017). We demonstrated that the A2 is specifically connected with the amygdala, which is consistent with the idea that A2 is a higher-order region in the mouse auditory cortex.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…This could be addressed via systematic projection mapping between the auditory cortex and the amygdala. In the current study, we visualized comprehensive connectivity between the auditory cortex and the amygdala by injecting cholera toxin subunit b (CTB), a bidirectional tracer, into four tonotopic regions of the auditory cortex, according to a map that was functionally determined using flavoprotein fluorescence imaging (Tsukano et al, 2017). We demonstrated that the A2 is specifically connected with the amygdala, which is consistent with the idea that A2 is a higher-order region in the mouse auditory cortex.…”
Section: Introductionsupporting
confidence: 76%
“…Overall, our findings endorse the notion that A2 is a higher-order auditory region in the mouse auditory cortex. The auditory subregions of DM, AAF, A1, and A2 have been found to be tonotopic (Tsukano et al, 2017), and all of these fields receive substantial projections from the lemniscal auditory thalamus of the ventral division of the medial geniculate body (MGv) (Tsukano et al, 2017;Ohga et al, 2018). Because the general concept explains that cortical areas that receive afferents from MGv are primary auditory areas, a question arises regarding whether these fields, including A2, are all primary areas in the mouse cortex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These will include the relatively low density laminar area of vGlut2 + fibers above the high intensity Cux1 + band (presumptive layers 2/3) in ACx, which can be distinguished from the dorsal area with a higher density of vGlut2 + fibers, and a relatively thick vGlut2 + band in the lower layers. The dorsal‐to‐ventral length of the Cux1 + patch in ACx was much longer than what would be expected for A1 (Llano & Sherman, ; Tsukano et al, ) and therefore will include other auditory cortical regions. More detailed analysis will be necessary to confirm this.…”
Section: Discussionmentioning
confidence: 91%